(untitled) (Research, Society and Development, 2021)
This article empirically assesses the effects of public spending on homicide rates in the Brazilian youth population. The study performs an approach with panel data in three models, pooled, fixed effect and random effect, by Brazilian federation units in the period 2002-2014. Using other explanatory variables, the impact of expenditure on assistance and social security on the juvenile homicide rate in the 15 to 29 age group is discussed. Based on the three different panel models, the results support the hypothesis that increases in these expenses produce reductions in the homicide rates of this population. The variables that represent poverty, education, unemployment, expenditure on justice and citizenship, electricity consumption and average income are also statistically significant in the study and, in general, confirm the expected signs.